The development of the welfare state in Portugal : trends in social expenditure between 1938 and 2003 - Carolo, Daniel Fernando (2022)
This paper presents a data series on social expenditure in Portugal for the period 1938-2003. The series was built with the aim of identifying and characterizing the most significant phases in the process leading up to the current welfare state system in this country. The establishment of a social insurance (Prevideˆncia) in 1935 was one of the founding pillars of the Estado Novo (New State). Reforms to Social Welfare (Prevideˆncia Social) in 1962, while in the full throes of the New State, policy measures taken after the revolution of 1974 and a new orientation for social policy following the accession of Portugal to the European Economic Community (EEC) in the mid-1980s brought about significant transformations in the institutional organizational structure that provided welfare and conferred social rights in Portugal. To understand this process, knowledge is needed of the transfor mations to the institutional structures governing the organizations that provided welfare, welfare coverage in terms of the type of benefit and the population entitled to social risk protection, the magnitude of spending on benefits associated with these risks, as well as how benefits were allocated between the institutions. We built a data series for the period 1938-1980, which can then be matched to data already published in the OECD Social Expenditure Database from 1980 onwards. As a result, a consistent series for social expenditure from 1938 to 2003 was obtained. The methodology used to create the series enabled us to measure the impact of the variation in population coverage for social risks and the average generosity of benefits on the relative share of social expenditure in GDP. We present an interpretive reading for the full period, covering the New State and the Democracy from 1974, of the process of building the welfare state in Portugal.